A 6 part action plan to transform food systems under climate change, Creative actions to accelerate progress towards the SDGs - Dinesh, Dhanush; Loboguerrero Rodriguez, Ana María; Millan, Alberto; Rawe, Tonya; Stringer, Lindsay; Thornton, Philip K.; Vermeulen, Sonja J.; Campbell, Bruce M. (2018)
If we are to achieve the Sustainable Development Goals (SDGs) related to poverty, climate change and food and nutrition security, the agricultural development community (research institutions, private sector, farmer organizations, national and international agencies) will have to work collectively with the world’s 700 million small-scale farmers by 2030 to transform the way food is produced, processed and consumed. Never before have we faced such ambitious goals.